Revision and transfer of Neotropical genera of the tribe Morimopsini Lacordaire, 1869 (Coleoptera: Cerambycidae): new species, redescription, taxonomic notes, and species key - Ávila-Jiménez, Ángelo (Zootaxa, 2024)
The transfer of Neotropical genera from Morimopsini to Apomecynini is proposed. Two new species are described, Tuberolamia santossilvai sp. nov. and Polytuberotum boteroi sp. nov. The unknown female of Tuberolamia andicola Breuning, 1940 is described and illustrated. Keys to species, distribution map, and taxonomic considerations for the group are provided.